2012
DOI: 10.1364/oe.20.024545
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pump and seed modulation on the mode instability thresholds of fiber amplifiers

Abstract: Using numerical simulations of thermally induced mode coupling we show how the instability threshold can be substantially reduced if the pump or injected signal is modulated in the kHz range. We also show how the mode coupling gain varies with the frequency offset of the parasitic mode. We model thresholds when the source of detuned light is quantum background, amplitude modulation of the pump power, and amplitude modulation of the signal seed. We suggest several key experimental and modeling tests of our mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
63
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 76 publications
(69 citation statements)
references
References 18 publications
5
63
0
1
Order By: Relevance
“…Quantum defect heating creates a temperature grating, and consequently a refractive index grating, that is responsible for coupling between the two fiber modes. Numerical models of the STRS process show that, like other stimulated Rayleigh scattering processes, the gain has a dispersive shape [6,7] similar to that shown in Fig. 1.…”
Section: Introductionsupporting
confidence: 59%
See 1 more Smart Citation
“…Quantum defect heating creates a temperature grating, and consequently a refractive index grating, that is responsible for coupling between the two fiber modes. Numerical models of the STRS process show that, like other stimulated Rayleigh scattering processes, the gain has a dispersive shape [6,7] similar to that shown in Fig. 1.…”
Section: Introductionsupporting
confidence: 59%
“…If the fundamental LP 01 mode is injected at the fiber input, slightly above the threshold the output is largely in LP 11 . This modal instability is caused by a stimulated thermal Rayleigh scattering (STRS) process [5,6,7]. Quantum defect heating creates a temperature grating, and consequently a refractive index grating, that is responsible for coupling between the two fiber modes.…”
Section: Introductionmentioning
confidence: 99%
“…The recent discovery of transverse mode instability (TMI) in high-power fiber amplifiers [1] has motivated experimental [2][3][4] and theoretical [5][6][7][8][9][10][11][12][13] efforts to characterize and explain this phenomenon. TMI manifests itself as an instability in which the signal power fluctuates on a ms timescale between the fundamental mode (FM) and the first few higher-order modes (HOMs) when the average signal power is increased above a certain threshold.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also showed large dependency between TMI threshold and system parameters such as seed or pump noise as well as cooling conditions [6,19]. Seed noise can contain discrete frequency components possibly larger than the RIN, that if located within the frequency band of the nonlinear coupling constant reduces the TMI threshold.…”
Section: Estimating Modal Instability Thresholdmentioning
confidence: 99%